Penguatan Keterampilan Entrepreneur Himpunan Mahasiswa Pendidikan Kimia Melalui Pendampingan Inovasi, Standarisasi, dan Repackaging Es Krim - Dini Hadiarti; Fitriani Fitriani; Nur Aulia Fitri (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
The lack of innovation and standardization in Serbato Ice Cream presents a major challenge to product development and market competitiveness. This community engagement program aimed to enhance product value through recipe modification, new variant creation, product standardization, and packaging redesign. The innovation included replacing the red coloring from serbat water with the natural blue pigment of butterfly pea flowers, adjusting the recipe for a smoother texture, and conducting tests on fat, protein, and microbiological content. Repackaging involved adding nutritional information, halal certification, and expiration dates. The results revealed that Bulato Ice Cream contained higher protein (12.45%) than Serbato Ice Cream (2.70%), while Serbato Ice Cream had a higher fat content (2.70%) than Bulato (2.34%). Microbiological analysis confirmed both products were free of bacterial contamination. Sensory tests showed that Bulato Ice Cream was preferred for its color, sweetness, and flavor, while Serbato Ice Cream was favored for its aroma and texture. These innovations not only improved product quality and safety but also contributed economically to HIMDIKIM through the commercialization of attractive, standardized local ice cream products